-6(6-x)+8=6-8(x+2)

Simple and best practice solution for -6(6-x)+8=6-8(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(6-x)+8=6-8(x+2) equation:


Simplifying
-6(6 + -1x) + 8 = 6 + -8(x + 2)
(6 * -6 + -1x * -6) + 8 = 6 + -8(x + 2)
(-36 + 6x) + 8 = 6 + -8(x + 2)

Reorder the terms:
-36 + 8 + 6x = 6 + -8(x + 2)

Combine like terms: -36 + 8 = -28
-28 + 6x = 6 + -8(x + 2)

Reorder the terms:
-28 + 6x = 6 + -8(2 + x)
-28 + 6x = 6 + (2 * -8 + x * -8)
-28 + 6x = 6 + (-16 + -8x)

Combine like terms: 6 + -16 = -10
-28 + 6x = -10 + -8x

Solving
-28 + 6x = -10 + -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
-28 + 6x + 8x = -10 + -8x + 8x

Combine like terms: 6x + 8x = 14x
-28 + 14x = -10 + -8x + 8x

Combine like terms: -8x + 8x = 0
-28 + 14x = -10 + 0
-28 + 14x = -10

Add '28' to each side of the equation.
-28 + 28 + 14x = -10 + 28

Combine like terms: -28 + 28 = 0
0 + 14x = -10 + 28
14x = -10 + 28

Combine like terms: -10 + 28 = 18
14x = 18

Divide each side by '14'.
x = 1.285714286

Simplifying
x = 1.285714286

See similar equations:

| V^2-6v-33=0 | | x(-1)=0 | | 2(x-6)=24-6(x+2) | | -24=-v/4 | | 4(7s+3)-3(6s+4)= | | 3x+4(5x-6)=(38) | | x^2-4y^2+2x+8y-31=0 | | c/12=15 | | (-2x+10)+(-8x-1)=10x+-9 | | w/5=-30 | | 10x-10=55 | | 3x^2-30=-9x | | 8n+3n= | | 1/4y=20 | | -(6x-1)+6x=11 | | x=140+1.3y | | 56=5u-14 | | 3x-4y=420 | | 141.5512=2*3.14*r*7.5+2*3.14*r^2 | | 35=-2x-15-3x | | 15x-20000=24000 | | -10x(x-5)=-8(x+9) | | 2=-9+w | | 13+(5a+3)= | | 2(9-1)-5a=7 | | 3x-4x=420 | | 45x^2+94x+48=0 | | ax-w=3forw | | 7x=9(2+x) | | 1x+500=1200 | | 7x+150=15x | | 34=2v+10 |

Equations solver categories